Perbandingan Kadar Karbohidrat Kecap Dengan Penambahan Air Kelapa Muda dan Air Kelapa Tua Pada Berbagai Konsentrasi - Hasyim, Ahmad; Purnamasari, A.Bida; Adolvina, Adolvina (Fakultas MIPA UNM, 2017)
This study aims to determine the content of carbohydrates in the manufacture of soy sauce with the addition of old coconut water and young coconut water. This research was conducted in the laboratory of Biology STKIP-PI Makassar and test of carbohydrate content in Biology Laboratory of Makassar State University. The method used in this research is Spectrophotometer method with wavelength 540 nm. Data obtained from carbohydrate test results were analyzed by using descriptive qualitative, the results showed that with the addition of coconut water effect on the carbohydrate content in the making of soy sauce with the highest carbohydrate content in coconut water soy sauce with the concentration of 15% is 7% carbohydrate level. The result of this research can be concluded that the higher concentration of old coconut water and young coconut water in the making of soy sauce, the higher the carbohydrate level. Keywords:Â soy sauce, coconut water, and carbohydrate level